The sociology of pottery in ancient Palestine : the ceramic industry and the diffusion of ceramic style in the Bronze and Iron Ages /: the ceramic industry and the diffusion of ceramic style in the Bronze and Iron Ages. (1990) - Unknown
No abstract available